2007
DOI: 10.1111/j.1349-7006.2007.00604.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of JTP‐70902, a p15INK4b‐inductive compound, as a novel MEK1/2 inhibitor

Abstract: The INK4 family members p16INK4a and p15 INK4b negatively regulate cell cycle progression by inhibition of cyclin-dependent kinase (CDK) 4/6. Loss of p16INK4a functional activity is frequently observed in tumor cells, and is thought to be one of the primary causes of carcinogenesis. In contrast, despite the biochemical similarity to p16 INK4a, the frequency of defects in p15INK4b was found to be lower than in p16 INK4a, suggesting that p15 INK4b-inductive agents may be useful for tumor suppression. Here we rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
52
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 43 publications
(53 reference statements)
1
52
0
Order By: Relevance
“…13,14). GSK1120212 is a DMSO solvate compound (ratio 1:1) with potent and ATP noncompetitive inhibition of MEK1/2 ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…13,14). GSK1120212 is a DMSO solvate compound (ratio 1:1) with potent and ATP noncompetitive inhibition of MEK1/2 ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1,2,6 During a high-throughput screening for compounds that can induce expression of the cyclin-dependent kinase (CDK) 4/6 inhibitor p15 INK4b , we identified 2 ( Figure 1). 7 Subsequent experiments confirmed that 2 has an antiproliferative activity against human cancer cell lines ACHN (renal adenocarcinoma) and HT-29 (colorectal adenocarcinoma) with IC 50 values of 4800 and 990 nM, respectively. We conducted a medicinal chemistry campaign, chemically modifying 2 to optimize for these antiproliferative effects.…”
mentioning
confidence: 89%
“…As a result, we found that 8b binds to MEK1/2 and inhibits its kinase activity with high specificity. 7,8,10,11 To confirm that cellular antiproliferative activity is due to cellular inhibition of MEK1/2 kinase activity, the DMSO solvate 1 was tested in both a cellular phospho-ERK1/2 assay and cell proliferation assays. In BRAF mutant SK-MEL-28 cells and KRAS mutant HCT116 cells, 1 caused dose-dependent inhibition of ERK1/2 phosphorylation as well as dose-dependent growth inhibition.…”
mentioning
confidence: 99%
“…Key toxicities include hyperglycemia, neuropsychiatric disorders, liver toxicity, skin rash and hypersensitivity, and gastrointestinal toxicity. Trametinib (GSK1120212; Mekinist) is a reversible, highly selective allosteric inhibitor of MEK1/MEK2 activation and kinase activity (11,12). MTD and RP2D of trametinib are 3 and 2 mg/d, respectively (13,14).…”
Section: Introductionmentioning
confidence: 99%